Relationship Between Perceived Usefulness, Ease Of Use And Satisfaction Among International Students Towards The Universiti Putra Malaysia Website - Ganji Ketab, Somayeh Mortazavi (2009)

(untitled)
An international university can communicate better with foreign users by an easy and useful website which its content replies to all students’ information needs. The lack of sufficient information for international students may happen in that kind of bilingual websites which all information has not been translated equally in both languages and the national language is dominant. This research aims to measure the level of ease of use and usefulness of the Universiti Putra Malaysia (UPM) website in order to know the foreign students' expectation and satisfaction with it and evaluate the content from the users’ point of view. The questionnaire survey was employed as the instrument for data collection in this study. Simple Random sampling technique was applied in the sample selection of the respondents. A self-administered questionnaire was designed as a research instrument in survey section. A total of 328 international students participated in the survey conducted in the Universiti Putra Malaysia. The return response rate was 92.1 percent. Statistical techniques engaged in survey study included frequency distribution, descriptive analysis statistics and Spearman rho Correlation coefficient. The results revealed that the level of ease of use and usefulness of the UPM website was high among international students. As the UPM website had English language problem for users, but they were satisfied with it and could communicate with website. Additionally, the findings indicated that there is a moderate correlation between ease of use of the UPM website and the international students' satisfaction, as the correlation between usefulness and users' satisfaction was high. It can be concluded that the respondents of this study perceived UPM website useful and easy to use and they are satisfied with it. Meaning an easy and useful technology has effects on users to accept or reject it. Based on this study a useful academic website with rich content is more interesting than an easy website for students. They expected to have access to a complete university website in order to answer to all information needs with more detailed information and it should be the first reference to get information from.